Prognostic and Predictive Factors of Mortality in Burn Patients at dr. Cipto Mangunkusumo General Hospital, Indonesia - Hasibuan, Muhamad Irfan A; Moenadjat, Yefta (The New Ropanasuri Journal of Surgery, 2021)
Introduction. Some prognostic– and predictive factors in burn have never been investigated in Indonesian specific characteristics, which is delayed treatment. A study was conducted to determine prognostic and predictive factors in this specific characteristic. Method. A retrospective cohort focused on burn mortality in extensive burns managed in CMGH from 1998–2010. Some known prognostic– and predictive factors and unknown ones were the variables of interest. Bivariate and multivariate using logistic regression analysis proceeded to find out these factors. Results. Out of all factors investigated, the variables that showed a significant correlation were: TBSA, inhalation injury, Baux score, revised Baux score, serum albumin, blood urea, serum creatinine, haemoconcentration, base excess, serum lactate, international normalized ratio, and random blood glucose. Conclusion. In the study, Baux score, revised Baux score, serum creatinine, haemoconcentration, base excess, and INR as predictive factors for mortality in the extensive burn.